ナンキョクカイ インドヨウ ク ニ オケル エイヨウ エン - 福井, 深; フクイ, フカシ; 山県, 健二; ヤマガタ, ケンジ; Fukui, Fukashi; Yamagata, Kenji (1981)
P(論文) 1979年12月から1980年3月にわたって実施された水産庁「開洋丸」によるインド洋南極海の調査航海において, オーストラリアと南極間の表面観測および東経100°～120°南緯61°以南に設定された調査海域の各層観測を行い, 栄養塩の分布を明らかにするため, 溶存酸素, リン酸塩, ケイ酸塩, 亜硝酸塩および硝酸塩を測定した。表面観測の結果, 亜熱帯収束線および南極収束線にて急激なる栄養塩の変動が明らかとなった。各層観測の結果は以下の通りであった。(1)硝酸塩, リン酸塩の鉛直変化は100～150m以深では非常に均一である。(2)100μg-at/L以上のケイ酸塩および5.0ml/L以下の酸素を示す等濃度線が63°～64°Sの表層へ向かい100～200m付近にまで分布している。これらの分布パターンは南極発散域における湧昇現象を示唆していると思われる。(3)硝酸塩とリン酸塩の比は15.2±0.6 : 1と南極海以外の海域に比較し高目の値を示した。 During the cruise of the R. V. KAIYO MARU (Fisheries Agency of Japan) in the Indian Sector of the Antarctic Ocean from December 1979 to March 1980,the surface observation between Australia and Antarctica and serial observation in the area bounded by 100°-120°E and 61°-65°S off the Budd Coast of Wilkes Land were carried out on board, in order to determine contents of dissolved oxygen, phosphate-phosphorus, silicate-silicon, nitrite-nitrogen and nitrate-nitrogen. Surface observation revealed marked longitudinal changes of nutrient matters related to the existence of the Subtropical Convergence and the Antarctic Convergence. Serial observation showed that distributions of nitrate and phosphate were quite homogeneous below the depth of 100-150m. Relatively low dissolved oxygen content and high silicate content were found up to 100m in the region of about 63°-64°S. This phenomenon may be attributed to the upwelling of water in the region of the Antarctic Divergence. The ratio of nitrate to phosphate in the sea off the Budd Coast was 15.2±0.6 : 1. This ratio was relatively higher than those in other oceans. departmental bulletin paper